Acetylcholinesterase studies as colonic pseudo-obstruction inhibitor on quercitrin from neem leaf extract (Azadirachta indica) - Abdul Ghani, Nur Hamizah; Satriawan, Herland; Yuhanda, Wismeri; Roikhan, Muhammad Abdillah; Rita, Rauza Sukma (LP2M Universitas Negeri Padang, 2023)
This research focuses on the study of Acetylcholinesterase (AChE) as an inhibitor of Colonic PseudoObstruction using Quercitrin obtained from neem leaf extract (Azadirachta indica). The research methods used include Pymol, Pyrex, Protein Plus, and Lipinski's rule. Analysis using Pymol and Pyrex resulted in Binding Affinity of -9.0, -8.8, and -8.7 and RMSD values of 0, 1.443, and 1.767 indicating a good potential interaction between AChE and Quercitrin. In this study, Protein Plus was used to identify the interaction between Quercitrin and AChE, the results showed a significant interaction between the two which may contribute in inhibiting Colonic Pseudo-Obstruction. Assessment of the physicochemical properties of Quercitrin using Lipinski's rule resulted in a molecular mass of 435, number of hydrogen bond donors 7, hydrogen bond acceptors 11, log P 0.000 and molar reactivity 0.000, indicating that Quercitrin meets the criteria to be an effective drug. Thus, the results of this study open up new prospects in the use of Quercitrin as a therapeutic agent in AChE inhibition for the treatment of Colonic Pseudo-Obstruction.